English Vocabulary Improvment Through Mobile Legend Game: English Vocabulary Improvment Through Mobile Legend Game Pelatihan Peningkatan Kosakata Bahasa Inggris Melaui Game Mobile Legends - Dharmawati, Dharmawati; Khair, Ummul; Suriati, Suriati; Sarudin, Sarudin; Pulungan, Sahmiar (Universitas Lancang Kuning, 2024)
Learning English can be done through digital media including online games and one of them is Mobile Legends game. The purpose of this community service activity is to provide English learning training to increase participants' vocabularies through Mobile Legends game. There are 3 methods used in this activity, namely the Leatoring Method, the Skill Training Method and the Discovery Method. The result of this activity is increasing English vocabularies and sentences knowledge after playing the Mobile Legends game. This is because the Mobile Legends game uses English, so little by little the player's knowledge of English vocabulary and sentences also increases. The implementation of this activity was said to be successful as seen from the enthusiasm and motivation and interest in learning English of the participants.